Ambient fine particulate matter (PM2.5) exposure is associated with idiopathic ventricular premature complexes burden: A cohort study with consecutive Holter recordings. (6th January 2019) - Tsai, Tsung‐Ying; Lo, Li‐Wei; Liu, Shin‐Huei; Cheng, Wen‐Han; Chou, Yu‐Hui; Lin, Wei‐Lun; Shinya, Yamada; Lin, Yenn‐Jiang; Chang, Shih‐Lin; Hu, Yu‐Feng; Chung, Fa‐Po; Liao, Jo‐Nan; et al.
Abstract: Background: Epidemiological evidence has shown an association between ambient fine particulate matter (PM2.5) exposure and cardiovascular mortality. Increased ventricular premature complex (VPC) burden can cause left ventricular dilatation and dysfunction. We aimed to investigate the relationship between acute PM2.5 exposure and VPC burden in patients without structural heart disease. Methods: We reviewed 26 820 patients who underwent 24‐hour Holter electrocardiogram (ECG) recordings between 1 Jan 2013 and 1 Dec 2016. We enrolled patients with significant idiopathic (structurally normal heart) VPC burden defined as ≥30 VPCs/h (Lown grade 2) who had at least two Holter ECG recordings. The VPC burden between the studies on high and low PM2.5 exposure dates was compared in 24 and 12 hours time periods. Result: Sixty‐seven patients (31 men, 56.49 ± 18.35 years) were enrolled. Patients were exposed to 25.63 ± 11.47 and 14.66 ± 7.51 μg/m 3 of PM2.5 during the high and low study dates, respectively. The overall VPC counts (10, 490.69 ± 10, 681.63/day) and burden (10.22% ± 10.17%) were significantly higher on the days with higher PM2.5 exposure compared with low PM2.5 exposure dates (8293.31 ± 9009.09; P  = 0.014% and 9.14% ± 12.73%, P  = 0.012, respectively). Compared with low PM2.5 exposure dates, the VPC burden on high exposure dates was significantly higher from 9am to 9pm  (5.85% ± 6.41% vs 4.84% ± 6.97%; P  = 0.025) but not at nocturnal periods. Conclusion: Our study demonstrated a significantly higher VPC burden on high PM2.5 exposure date. The burden was increased in the daytime but not at nighttime. This result suggests that daytime PM2.5 exposure may be associated with ventricular arrhythmia burden in the healthy population.